THE PRINCIPLE OF MAQASHID SHARI'AH IN HANDLING COVID-19 PANDEMIC IN INDONESIA - Fuad Fuad; Said Munawar (Qistie Jurnal Ilmu Hukum, 2023)
The pandemic of Covid-19 has presented an almost evenly distributed continuity and fear in every aspect of human life around the world. Covid-19 triggered several things, for example, related to economic activity, the implementation of education, the implementation of public services, and so on. There have been many casualties caused by the emergence of the pandemic around the world. The method used in this study is normative juridical with a statute approach and a conceptual approach. The purpose of Islamic Law or maqashid al-shari'ah is a shari'a that is determined and intended for the benefit of man in the world and the Hereafter. Shari'a is structured to realize the happiness of individuals and pilgrims (human beings), maintain the rules and enliven the world with all means, and will continue it at the glorious levels of perfection, culture, goodness, and civilization, because Islamic proselytizing is a mercy for all mankind, namely achieving benefit, goodness, and pleasure over humans and avoiding or preventing damage or ugliness. The handling of the Covid-19 pandemic has been carried out by the government by the principles regulated in maqashid al-sharia, namely tasarruf al-imam 'ala al-raiyyah and hifdzun an nafs.